2015
DOI: 10.5114/wo.2015.56651
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cells predict survival in gastric cancer patients: a meta-analysis

Abstract: Aim of the studyThe prognostic value of the detection of circulating tumour cells (CTCs) in gastric cancer has been studied intensely in recent years. However, the application of different technologies led to inconsistent results between the studies. Here, we performed a meta-analysis of published studies to summarise the evidence.Material and methodsMedline and ISI Web of Knowledge were searched up to March 2013 using “circulating tumor cells” and “gastric cancer” as search terms. Hazard ratio (HR) with 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
(64 reference statements)
3
7
1
Order By: Relevance
“…The enumeration of CTCs is particularly important in gastric cancer, which is the second leading cause of cancer-related death worldwide. Our current data indicate that detection of CTCs may indeed be a useful prognostic indicator for use in patients with gastric cancer, and are consistent with previous reports[25,26]. …”
Section: Discussionsupporting
confidence: 93%
“…The enumeration of CTCs is particularly important in gastric cancer, which is the second leading cause of cancer-related death worldwide. Our current data indicate that detection of CTCs may indeed be a useful prognostic indicator for use in patients with gastric cancer, and are consistent with previous reports[25,26]. …”
Section: Discussionsupporting
confidence: 93%
“…The result of our meta-analysis solved the controversies from two independent meta-analyses [7, 9] and demonstrated the prognostic role of CTCs detected by cytological methods in gastric cancer. Cytological methods may avoid false positive results from nonneoplastic and contaminated samples which was frequent in molecular methods, and they were able to count the number of CTCs and recognize viable and functional CTCs [33], so they may provide us with a more accurate result by using the cytological methods.…”
Section: Discussionmentioning
confidence: 63%
“…Currently, the major techniques used to identify CTCs can be divided into two aspects, the cytological methods (such as CellSearch, immunocytochemistry, flow cytometry, and immune-magnetic and fluorescence-activated cell sorter) and the molecular methods (mainly the PCR) [3]. Although meta-analyses have shown that the presence of CTCs in peripheral blood of patients with gastric cancer was associated with poor prognosis and clinical characteristics [79], most studies involved in these meta-analyses used the molecular methods and the prognostic value of CTCs detected by cytological methods remains controversial. The pooled HR on OS from two meta-analyses showed different results for CTCs positive patients when detected by cytological methods (HR = 2.00, 95% CI: 0.1.28–3.13 [7]; HR = 1.67, 95% CI: 0.57–4.92 [9], resp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding treatment response, a meta-analysis considering 12 relevant studies demonstrated that prior to treatment CTCs correlated with lymph node status, distant metastasis, and disease staging, however, post-treatment CTCs only correlated with staging (Ma et al, 2012). Including the earlier mentioned meta-analysis, a number of meta-analyses were conducted in different cancers such as gastric cancer (Wang, Wei, Zou, Qian, & Liu, 2016), metastatic breast cancer (Lv et al, 2016), ovarian cancer (Cui, Kwong, & Wang, 2015; Zhou et al, 2015), head and neck (Wang, Cui, Xue, Tong, & Li, 2015), colorectal cancer (Huang et al, 2015), liver cancer (Jin, Peng, & Wu, 2013), prostate cancer (Wang et al, 2011), bladder and urothelial cancer (Wang et al, 2011), and positive correlations with CTCs were established.…”
Section: Approaches Used To Detect Metastatic Lesions (On a Clinicmentioning
confidence: 99%